Safety and effectiveness of mass drug administration to accelerate elimination of artemisinin-resistant falciparum malaria: A pilot trial in four villages of Eastern Myanmar - Landier, J; Kajeechiwa, L; Thwin, M; Parker, D; Chaumeau, V; Wiladphaingern, J; Imwong, M; Miotto, O; Patumrat, K; Duanguppama, J; Cerqueira, D; Malleret, B; et al. (Wellcome Trust, 2017)
Background: Artemisinin and partner drug-resistant falciparum malaria is expanding over the Greater Mekong Sub-region (GMS). Eliminating falciparum malaria in the GMS while drugs still retain enough efficacy could prevent global spread of antimalarial resistance. Eliminating malaria rapidly requires targeting the reservoir of asymptomatic parasite carriers. This pilot trial aimed to evaluate the acceptability, safety, feasibility and effectiveness of mass-drug administration (MDA) in reducing malaria in four villages in Eastern Myanmar. Methods: Villages with ≥30% malaria prevalence were selected. Long-lasting insecticidal bednets (LLINs) and access to malaria early diagnosis and treatment (EDT) were provided. Two villages received MDA immediately and two were followed for nine months pre-MDA. MDA consisted of a 3-day supervised course of  dihydroartemisinin-piperaquine and single low-dose primaquine administered monthly for three months. Adverse events (AE) were monitored by interviews and consultations. Malaria prevalence was assessed by ultrasensitive PCR quarterly for 24 months. Symptomatic malaria incidence,entomological indices, and antimalarial resistance markers were monitored. Results: MDA was well tolerated. There were no serious AE and mild to moderate AE were reported in 5.6%(212/3931) interviews. In the smaller villages, participation to three MDA courses was 61% and 57%, compared to 28% and 29% in the larger villages. Baseline prevalence was higher in intervention than in control villages (18.7% (95%CI=16.1-21.6) versus 6.8%(5.2-8.7), p<0.0001) whereas three months after starting MDA, prevalence was lower in intervention villages (0.4%(0.04-1.3) versus 2.7%(1.7-4.1), p=0.0014). After nine months the difference was no longer significant (2.0%(1.0-3.5) versus 0.9%(0.04-1.8), p=0.10). M0-M9 symptomatic falciparum incidence was similar between intervention and control. Before/after MDA comparisons showed that asymptomatic P. falciparum carriage and anopheline vector positivity decreased significantly whereas prevalence of the artemisinin-resistance molecular marker remained stable. Conclusions: This MDA was safe and feasible, and, could accelerate elimination of P. falciparum in addition to EDT and LLINs when community participation was sufficient.